Nano composite fiber process optimization for polypropylene with antibacterial and far-infrared ray emission properties. Issue 16 (October 2016) - Kuo, Chung-Feng Jeffrey; Fan, Chih-Chia; Su, Te-Li; Chen, Shih-Hsiung; Lan, Wei Lun
This research aims to develop multifunctional polypropylene (PP) fiber with a far-infrared ray emission property and microorganism resistance. The processing parameters, including powder proportion, twin-screw mixing and melt spinning, were planned using the Taguchi method, gray relational analysis and the technique for order preference by similarity to ideal solution. The emission test results showed that the far-infrared ray emission value of composite fiber was 85%, which is 2.3 times that of pure PP. According to the far-infrared ray emission temperature rise test, the composite fiber temperature increases by 8.6℃, which is 43% higher than the 6℃ temperature rise of pure PP. The antibacterial test showed that the composite fiber has an antibacterial effect on staphylococcus aureus and pneumobacillus. Moreover, the composite fiber of PP with nano silicon dioxide and zinc oxide met the far-infrared ray emission property FTTS-FA-010 and qualitative antibacterial JIS L-1902 standards.